THE APPLICATION OF MICROCONTROLLER BASED SYSTEM TO DESIGN OF ELECTRO MECHANICAL MANIPULATOR STICK - Mei Edi Prayitno; Aab Abdul Wahab; Muhammad Zulkifli (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Independence and advancement of defense equipment in our country demands the professional and high dedication of TNI soldiers, especially the Navy. A soldier must be able and master, operate, and maintain and can solve any problems arising either due to usage or due to technical errors that occur on defense equipment both in operation and hombase. In practice grenade throwing on the field are often found unexploded grenades after being thrown. At this time the handling of unexploded grenades is detonated on the spot, however the tool used to locate the crushing explosives is still very traditional by using bamboo poles. In this final project there will be a tool for placing crushing explosives on unexploded grenade handling procedures in the field, using a long, folded, robotic arm stick that is driven by a gearbox motor, the mechanism of this tool will be made with the arm system using Electromechanical systems. At the end of the stick is installed gripper which serves to clamp the explosives before being placed on unexploded grenades. Stick Manipulator to be created can assist trainers and instructors in the implementation of explosive placement on unexploded grenade handling procedures on target and can be an additional tool of equipment owned by current trainers and instructors and can be useful for units in need , And held a grenade throwing exercise.